Algorithmic Decision-Making in Service Work: An Analysis of Changing Job Autonomy - Gina Glock (Nomos, 2024)
Far-reaching transformations in the world of work are being discussed vividly under the term 'artificial intelligence'. Questions are arising about the changing role of humans in work processes and their freedom to determine work content and conditions. This book explores these potential areas of conflict and examines how algorithmic decision-making systems influence the job autonomy of service workers. Using case studies from outpatient care and banking services, this book shows under which organisational conditions positive experiences of autonomy are enabled. Dr Gina Glock is a work sociologist, who researches the interplay of work and digitalisation.
Keywords: 300; Artificial Intelligence; AI; digital transformation; ADM; Deep Learning; service work; digital labour; information technologies; sociology of work; industrial sociology; Algorithmic Decision-Making; Banking services; Care Work; Digitalization of work; Job Autonomy; Labour Research; Digital Taylorism